Long‐term effects of plant diversity and composition on plant stoichiometry. Issue 5 (22nd September 2015) - Guiz, Jordan; Hillebrand, Helmut; Borer, Elizabeth T.; Abbas, Maike; Ebeling, Anne; Weigelt, Alexandra; Oelmann, Yvonne; Fornara, Dario; Wilcke, Wolfgang; Temperton, Vicky M.; Weisser, Wolfgang W.
Abstract : Plant elemental composition can indicate resource limitation, and changes in key elemental ratios (e.g. plant C:N ratios) can influence rates including herbivory, nutrient recycling, and pathogen infection. Although plant stoichiometry can influence ecosystem‐level processes, very few studies have addressed whether and how plant C:N stoichiometry changes with plant diversity and composition. Here, using two long‐term experimental manipulations of plant diversity (Jena and Cedar Creek), we test whether plant richness (species and functional groups) or composition (functional group proportions) affects temporal trends and variability of community‐wide C:N stoichiometry. Site fertility determined the initial community‐scale C:N ratio. Communities growing on N‐poor soil (Cedar Creek) began with higher C:N ratios than communities growing on N‐rich soil (Jena). However, site‐level plant C:N ratios converged through time, most rapidly in high diversity plots. In Jena, plant community C:N ratios increased. This temporal trend was stronger with increasing richness. However, temporal variability of C:N decreased as plant richness increased. In contrast, C:N decreased over time at Cedar Creek, most strongly at high species and functional richness, whereas the temporal variability of C:N increased with both measures of diversity at this site. Thus, temporal trends in the mean and variability of C:N were underlain by concordant changes among sites in functional group proportions. In particular, the convergence of community‐scale C:N over time at these very different sites was mainly due to increasing proportions of forbs at both sites, replacing high mean C:N (C4 grasses, Cedar Creek) or low C:N (legumes, Jena) species. Diversity amplified this convergence; although temporal trends differed in sign between the sites, these trends increased in magnitude with increasing species richness. Our results suggest a predictive mechanistic link between trends in plant diversity and functional group composition and trends in the many ecosystem rates that depend on aboveground community C:N. Synthesis We compared the effect of plant diversity on the temporal dynamics of community stoichiometry in two long‐term grassland diversity experiments: the Cedar Creek and Jena Experiments. Changes in community C:N ratios were accelerated by increasing diversity at both sites, but in opposite directions depending on soil fertility. Stoichiometry changes were driven by shifts of functional group composition differing in their elemental compositions, the identity of the functional groups depending on the site. Thus, we highlighted that community turnover constrained the effect of diversity on plant stoichiometry at both sites